Effect of bacteria in soil towards the corrosion of water-pipeline: a review - N.A.H. Abdul Haris; Sitti Fatimah Mhd. Ramle; Muhammad Azwadi Sulaiman; Mohamad Najmi Masri (Universiti Malaysia Kelantan, 2015)
Corrosion is a process of deterioration of metal surfaces where the metals were degraded into another compound. Soil is one of the medium known to have constituted to corrosion of metals. The soil creates an environment for the movement of electrons. The level of corrosion in soil can vary from major material loss or to minor effects. The buried pipelines are exposed to the soil that may experience corrosion attack. The study of the soil as a corrosive environment is important to mitigate the problem which may be serious to the environment and economy. There are few factors that contribute to the corrosion processes. This review focuses only to sulfate and sulfate reducing bacteria in soil. Hence, this review investigates the relationship of sulfate and sulfatereducing bacteria in soil.